MEMBANGUN JIWA ENTREPRENEURSHIP DALAM PERSPEKTIF EKONOMI SYARIAH - Savriadi,; Susi Marni,; Julisman, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
Efforts to grow or build entrepreneurship today are no longer the only things that need to be done, but are things that must or must be done by everyone. This obligation is caused more by the urgent need for someone to get out of economic weakness. This study analyzes about building entrepreneurship in the perspective of Islamic economics. This research method uses library research with qualitative descriptive data analysis with data processing techniques using inductive and deductive methods. The results of the study explain that Islamic entrepreneurship is all business activities that are carried out commercially in order to produce goods or services in a way that does not conflict with Islamic law. Building entrepreneurship in an Islamic economic perspective is developing characters that are disciplined, independent, realistic, committed, honest, and productive, to realize benefits that can bring blessings and continue to run their business by paying attention to the balance of life in the world and the hereafter. This character will have an impact on entrepreneurs to always maintain their business properly and not carry out business activities that harm other people, such as destroying other people's businesses in the wrong way